Performance and emissions of a series hybrid vehicle powered by a gasoline partially premixed combustion engine. (5th March 2019) - García, Antonio; Monsalve-Serrano, Javier; Sari, Rafael; Dimitrakopoulos, Nikolaos; Tunér, Martin; Tunestål, Per
Highlights: Battery state of charge optimized for two vehicles by means of design of experiments. More operating points needed from the combustion engine as vehicle weight increases. The hybrid concept is Euro 6 compliant with a small amount of urea. Abstract: This work evaluates the performance and emissions of the series hybrid vehicle concept powered by a gasoline partially premixed internal combustion engine. To do so, experimental data was collected from a Volvo VED-D4 Euro 6 four-cylinder compression ignition engine running under gasoline partially premixed combustion. Two series hybrid vehicle models were developed in GT-Power®, which were fed with the experimental data to evaluate the potential of the hybrid concept. First of all, the battery charging strategy of the hybrid vehicles was optimized in terms of number of power levels and operating conditions. For this, a design of experiments was performed in GT-Power®, which enabled to obtain a predictive model of the performance and emissions. The predictive model was used to obtain the optimized NOx-fuel consumption Pareto frontiers for each charging strategy proposed. Finally, the GT-Power® vehicle models were run with the optimal operating conditions (selected from each Pareto) in both the new European driving cycle and worldwide harmonized light vehicles test cycle. The results show that the hybrid powertrain running with partially premixed combustion is able to achieve similar or better performance than the commercial diesel vehicle with low engine-out emissions. Moreover, comparing the results from both vehicles, it was confirmed that the hybridization results in better improvements when applied to urban traffic than for highway conditions where the power request is higher and the potential for regenerative braking is reduced.